Investigation of meropenem stability after reconstitution: the influence of buffering and challenges to meet the NHS Yellow Cover Document compliance for continuous infusions in an outpatient setting. Issue Volume 27:Issue e1(2020) (13th January 2019) - Jamieson, Conor; Allwood, Michael Charles; Stonkute, Donata; Wallace, Andrew; Wilkinson, Alan-Shaun; Hills, Tim
Abstract : Objectives: To determine the influence of different buffers, pH and meropenem concentrations on the degradation rates of meropenem in aqueous solution during storage at 32°C, with the aim of developing a formulation suitable for 24-hour infusion in an ambulatory elastomeric device, compliant with the latest National Health Service Pharmaceutical Quality Assurance Committee Yellow Cover Document (YCD) requirements. Methods: Meropenem was diluted to 6.25 mg/mL and 25 mg/mL in aqueous solutions adjusted to various pH with phosphate or citrate buffer and assessed for stability. Meropenem concentrations were determined using a validated stability-indicating high-performance liquid chromatography method at time 0 and following storage for up to 24 hours at 32°C as per the YCD requirements. Results: Degradation was observed to be slowest in citrate buffer around pH 7 and at a meropenem concentration of 6.25 mg/mL; however, losses exceeded 10% after storage for 24 hours at 32°C in all of the diluents tested in the study. Conclusions: Meropenem at concentrations between 6.25 mg/mL and 25 mg/mL as tested is not sufficiently stable to administer as a 24-hour infusion in ambulatory device reservoirs. If the YCD 95% minimum content limit is applied, the infusion period must be reduced to less than 6 hours for body-worn devices, especially at the higher concentration studied (25 mg/mL). This limits the possibility of using elastomeric devices to deliver continuous infusions of meropenem as part of a wider outpatient parenteral antimicrobial therapy service.